The three Rs: Resources, reform, and reason?. (1st July 2012) - Hay, Peter
<x xml:space="preserve">Abstract</x> The introduction of Community care put the development of a market in adult social care to the fore. The emphasis of recent years upon personalized care put the choice and control by individuals at the heart of care services. Both policies require a major shift way from the model where the state prescribed the way services were delivered, and therefore largely provided the service itself. A new model is required which shapes and makes markets from which choices can be made. Despite these policy drivers, there has been a paucity of thinking about the role of the state in ensuring that markets provides the choice, quality and safety needed by citizens. As we develop the response to the Care and Support Bill there is a real opportunity to develop new approaches to markets as central to the exercise of individual choice.